Studi Pengaruh Penggunaan Campuran Abu Fiber Kelapa Sawit dan Semen Untuk Stabilisasi Tanah Lempung - Mildawati, Roza; Hidayat, Rizqi Wahyu (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2023)
Clay soils are susceptible to changes in moisture content, often experience instability in supporting the load above it, and have a large swelling potential. This study aimed to determine the effect of using palm fiber ash and cement for soil stabilization. This research method is divided into 2 processes of preserving test objects: CBR without soaking (unsoaked) for 0 days and 7 days and CBR soaked (soaked) for 4 days. The mixture variations used were 10%, 15%, 20% palm fiber ash and 7.5% cement. The MDD value was 1.468 g and OMC was 22%. The CBR value without soaking the original soil increased from 10.34% to 18.05% at 7 days of curing. The highest CBR value was obtained in a mixture of 10% palm fiber ash and 7.5% cement at 20.30% at 0 days of curing. The highest CBR value was obtained in a mixture of 10% palm fiber ash and 7.5% cement at 57.34% at 7 days of curing. The soaking CBR value tended to increase from 2.21% to 31.02% in the variation of 20% palm fiber ash and 7.5% cement mixture. The swelling potential value tends to decrease from 0.312% to 0.062%.